DETERMINAN ADOPSI TEKNOLOGI PERTANIAN OLEH PETANI KECIL DI NEGARA BERKEMBANG: PERSPEKTIF DAN PROSPEK UNTUK INDONESIA / Determinants of Agricultural Technology Adoption by Smallholder Farmers in Developing Countries: Perspective and Prospect for Indonesia - Suprehatin Suprehatin (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
The role of agricultural technology is important in developing countries. However, in many cases the adoption rate of modern agricultural technology by smallholder farmers is low. Therefore, a better understanding of agricultural technology adoption determinants is important as a major component of agricultural growth. This paper is a review and synthesize of the literature related to potential factors that may constrain or encourage smallholder farmer adoption of new agricultural technologies. The determinant factors influencing smallholder farmer adoption of new technologies in developing countries vary from study to study based on contextual applicability and specific local condition. There are four major typologies of determinant factors are identified to help explain low adoption rates of particular agricultural technology in developing countries which are technology attributes, farmer or farm household characteristics, farm characteristics and institutional factors. Future policy recommendations on adoption decision should consider all those four important factors to provide better understanding of new agricultural technology adoption by smallholder farmers, resulting in improved livelihoods for smallholders.Keywords: Agricultural, technology, adoption, farmer AbstrakPeran teknologi pertanian sangat penting di negara berkembang. Meskipun demikian, tingkat adopsi teknologi pertanian baru oleh petani kecil masih rendah. Oleh karena itu, pemahaman terhadap faktor-faktor yang menentukan keputusan petani dalam mengadopsi teknologi sangat penting untuk meningkatkan pertumbuhan sektor pertanian. Tulisan ini adalah hasil sintesis terhadap beberapa literatur ilmiah yang berkaitan dengan faktor penghambat atau pendorong petani kecil dalam mengadopsi teknologi pertanian. Faktor yang memengaruhi petani kecil mengadopsi teknologi pertanian di negara berkembang berbeda antarstudi berdasarkan kebutuhan dan kondisi lokal tertentu. Empat kelompok utama faktor penentu yang dapat menjelaskan rendahnya adopsi teknologi di negara berkembang yaitu atribut teknologi, karakteristik petani, usaha tani, dan faktor kelembagaan. Rekomendasi kebijakan terkait keputusan adopsi teknologi seharusnya mempertimbangkan keempat kelompok faktor tersebut untuk dapat memahami lebih baik adopsi teknologi baru oleh petani kecil guna meningkatkan kesejahteraannya.Kata kunci: Pertanian, teknologi, adopsi, petani